PREVALENCE AND PATTERN OF DYSLIPIDAEMIA AND ASSOCIATED FACTORS IN NAÏVE TYPE 2 DIABETES MELLITUS PATIENTS: A CROSS-SECTIONAL STUDY FROM WESTERN UTTAR PRADESH - DUBE, MUKESH; SINGH, SUNDAR PAL; KHARE, NEERAJ (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study was conducted with an objective to study prevalence and pattern of dyslipidemia in newly diagnosed type 2 diabetes mellitus patients. Methods: From August 2021 to March 2022, 161 participants participated in the trial. After a night of fasting, skilled medical laboratory technicians drew 5 ml of blood from each study subject and performed anthropometric measurements on them. Results: 110 patients, or 68.9% of the entire group, had dyslipidemia. About 3.7% (n=6) of the individuals had atherogenic dyslipidemia. Among 2.5% and 23.6% of the participants, high TC (total cholesterol) and low HDL (high-density lipoprotein), respectively, were found to be isolated dyslipidemias. Significantly more hypertensives (77.9%), people with abnormal fasting glucose levels (80.2%), those with elevated postprandial glucose levels (78.8%), and people with larger waist circumference had dyslipidemia (76.0%). Conclusion: Our study showed that diabetic patients have a significant prevalence of dyslipidemia. The main public health issue in underdeveloped nations is dyslipidemia, which also serves as a standalone risk factor for developing cardiovascular disease (CVD). In addition, it complicates the progression of CVD in diabetic individuals and raises mortality when combined with other risk factors like high blood pressure.